2020
DOI: 10.3892/ol.2020.11331
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinicopathological features and prognoses of patients with schistosomal and nonschistosomal colorectal cancer

Abstract: Patients with schistosomal colorectal cancer (CRC) and nonschistosomal CRC have different clinicopathological features, laboratory test results and survival rates. Long-term infection with schistosomiasis in patients with CRC may affect the pathogenesis and subsequently change the mechanisms of CRC in these patients, resulting in changes in the survival rates of patients with schistosomal and nonschistosomal CRC. In China, the most common type of schistosomiasis is S. japonicum. The present study aimed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
5
15
0
Order By: Relevance
“…The association between schistosomiasis and clinicopathological characteristics was evaluated by using the chi-square and Fisher's exact tests (Table 3). The Qingpu District of Shanghai was previously predominantly rural and, as more males were engaged in farm work, is likely to be at greater risk for exposure [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The association between schistosomiasis and clinicopathological characteristics was evaluated by using the chi-square and Fisher's exact tests (Table 3). The Qingpu District of Shanghai was previously predominantly rural and, as more males were engaged in farm work, is likely to be at greater risk for exposure [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there is also a male predominance(61%, Table 1) in the cohort, although there was no signi cant difference between CRC-NS and CRC-S patients (Table 3). Given Qingpu district of Shanghai is previously a countryside, more males engage in farm work, and they may be at greater risk for exposure [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested that schistosomal colitis is more commonly associated with an earlier onset of multicentric CRC, high percentage of mucinous adenocarcinoma, and presents at an advanced stage 19 . Another recently published report demonstrated that S. japonicum infection facilitates the development of CRC, particularly in the early and intermediate stages, suggesting that schistosomiasis may alter the mechanisms underlying the progression of CRC 22 . Nevertheless patients with schistosomal and nonschistosomal CRC, had the same outcome after 7.5 years 22 .…”
Section: Introductionmentioning
confidence: 99%